Color and nitrogen removal from synthetic dye wastewater in an integrated mesophilic hydrolysis/acidification and multiple anoxic/aerobic process. (December 2018) - Gu, Mengqi; Yin, Qidong; Wang, Zhongzhong; He, Kai; Wu, Guangxue
Abstract: Dye wastewater is one kind of refractory pollutant and it is commonly treated by the integrated anaerobic and aerobic process. A new integrated hydrolysis/acidification and multiple anoxic/aerobic (AO) process was proposed for the removal of color and nitrogen from azo dye wastewater. System performance, the degradation pathway of azo dye and nitrogen metabolic pathway were investigated with quadrupole-time-of-flight and metagenomic analyses. The proposed process removed color and nitrogen efficiently, with the removal percentages of 89.4% and 54.0%, respectively. A colorful intermediate C16 H11 N3 O7 S2 during the degradation of azo dye was detected. Controlling a low dissolved oxygen concentration in the multiple AO process could enhance nitrogen removal. The detected bacteria possessing azoreductase for the azo dye degradation included Desulfovibrio aminophilus, Thermoanaerobacter, Lactococcus raffinolactis, Ruminiclostridium and Rhodopirellula . The nitrifying genes of amo and hao were mainly detected in Nitrosomonas, while the denitrifying genes were detected in Thauera, Candidatus Accumulibacte r and Rhodothermus marinus . Highlights: Hydrolysis/acidification and multiple AO process removed color and N effectively. The color removal efficiency was enhanced under high COD concentrations. Low DO in the multiple AO reactor induced high nitrogen removal. A colorful intermediate was detected during RR2 degradation. Microbial communities were analyzed by high throughput sequencing and metagenomics.